Youth and bridging social capital of risk multi-ethnic society in Pasir Gudang, Johor. - Aizathul Hani Abd Hamid; Kamri, Khairol Anuar (Advances in Humanities and Contemporary Studies, 2020)
Social relationships among youth are essential as a basis for their social and emotional support. Social connections also enable young people to access resources owned by others for the survival of youth in today’s challenging life. In the multi-ethnic country, connection with other ethnic may open wider opportunities to youth. Bridging social capital is seen as having the potential to grow the youth’s potential by connecting youth with the wider community. Therefore, this article’s purpose is to identify the bridging social capital among Pasir Gudang youth with a multi-ethnic society outside the Pasir Gudang community. This study applied a survey method through the distribution of a set of questionnaires to 400 youth (Malay 60%, Chinese 25%, and Indian 15%) in Pasir Gudang, Johor. The respondent is chosen by using a stratified sampling method according to their Rukun Tetangga association in the Pasir Gudang community. Results were derived from the analyzed distribution of the questionnaire using version 23 of SPSS. The result showed that the Indian youth in Pasir Gudang has more bridging social capital as well as the trust, cohesive and reciprocity elements.